2011
DOI: 10.1007/s12576-011-0162-y
|View full text |Cite
|
Sign up to set email alerts
|

Heat acclimation-induced changes in heart glycogen/glucose metabolism in rats

Abstract: Based on the observation that heat acclimation is a slowly developing response, evoked by continuous exposure to moderate heat, we investigated the time-dependent acclimatory changes of heart glycogen metabolism. Cardiac levels of key carbohydrate-related enzymes and substrates were studied in the function of the duration of short-term (STHA; 6, 12, 24 and 48 h) and long-term heat acclimation (LTHA; 7, 14, 21 and 30 days) to high environmental temperature (35 ± 1°C). The changes in heart glycogen metabolism du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Prolonged heat exposure resulted in a prominent decrease of Tre in the HA group (Figure 1C). These findings are consistent with those of earlier studies conducted on HA rats (Dervisevik et al, 2011; Nakagawa et al, 2016).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Prolonged heat exposure resulted in a prominent decrease of Tre in the HA group (Figure 1C). These findings are consistent with those of earlier studies conducted on HA rats (Dervisevik et al, 2011; Nakagawa et al, 2016).…”
Section: Resultssupporting
confidence: 94%
“…Rats were randomly distributed into HA or C group. HA group was maintained in chamber temperature of 35 ± 1°C with a relative humidity of 55 ± 5% 2 h daily for 30 days to induce homeostasis and their body weight Tre changes were monitored (Dervisevik et al, 2011; Domazetovska et al, 2011; Alexander-Shani et al, 2017). Tre was measured under the arousal condition of food and water ad libitum .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these physiological, biochemical, and molecular responses make the animal survive in a harsh and stressful environment [14]. The study performed in mice showed that heart glucose level changes as a response to heat stress within a different period (12 and 24 h) of exposure to heat stress [15]. Besides, the study performed in chicken revealed that the apical glucose absorption in the jejunum is elevated to compensate for the glucose level in blood during heat stress [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac levels of key carbohydrate-related enzymes and substrates were studied in the function of the duration of short-term (STHA; 6, 12, 24 and 48 h) and long-term heat acclimation (LTHA; 7, 14, 21 and 30 days) to high environmental temperature (35 ± 1°C). The results obtained have showed that acclimation to moderate hyperthermic environment has caused significant changes in examined parameters which differ depending on duration to the exposure: intensive stress-induced glycogenolytic and glycolytic processes in the period of STHA and intensive energy sparing, manifested by Glk deposition in the period of LTHA [21].…”
Section: Discussionmentioning
confidence: 98%